Deteksi Virus Utama Bawang Merah dan Bawang Putih dari Daerah Jawa Barat dan Jawa Tengah - Kadwati Kadwati; Sri Hendrastuti Hidayat (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Viral disease has been reported to cause significant effect on production of shallot (A. cepa) and garlic (A. sativum). The study was conducted to detect main viruses from leaves and bulbs of shallot and garlic using specific antibodies by ELISA method. Leaf and bulb samples was collected from West Java (Bandung, Bogor and Cirebon), Central Java (Brebes), and Yogyakarta (Bantul). Single as well as mix infection of GCLV, SLV, and Potyvirus was successfully detected using specific antibodies. The average percentage of virus infection in the crop ranged from 11.2–14.3% on shallot, and 14.3% on garlic; whereas in the bulb ranged from 11.2–13.3% on shallot, and 9.18% on garlic.